2014
DOI: 10.1128/jvi.01859-13
|View full text |Cite
|
Sign up to set email alerts
|

Natural Single-Nucleotide Polymorphisms in the 3′ Region of the HIV-1 pol Gene Modulate Viral Replication Ability

Abstract: We previously showed that prototype macaque-tropic human immunodeficiency virus type 1 (HIV-1) acquired nonsynonymous growth-enhancing mutations within a narrow genomic region during the adaptation process in macaque cells. These adaptive mutations were clustered in the 3= region of the pol gene, encoding a small portion of the C-terminal domain of integrase (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 56 publications
2
50
0
Order By: Relevance
“…Subsequent virological studies of these mutations showed that in human lymphocyte cell lines, growth phenotypes of not only prototype macaque cell-tropic HIV-1s but also human cell-tropic HIV-1 (NL4-3 clone) were markedly altered by the introduction of naturally occurring single-nucleotide variations (Y226tac, D229gat, P233cct, and V234gtg) into SA1prox ( Fig. 2A) (6). Since the common and unique characteristics of these variants relative to the parental clones were their altered vif mRNA levels (6), we determined the expression levels of the Vif protein for each NL4-3 derivative.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequent virological studies of these mutations showed that in human lymphocyte cell lines, growth phenotypes of not only prototype macaque cell-tropic HIV-1s but also human cell-tropic HIV-1 (NL4-3 clone) were markedly altered by the introduction of naturally occurring single-nucleotide variations (Y226tac, D229gat, P233cct, and V234gtg) into SA1prox ( Fig. 2A) (6). Since the common and unique characteristics of these variants relative to the parental clones were their altered vif mRNA levels (6), we determined the expression levels of the Vif protein for each NL4-3 derivative.…”
Section: Resultsmentioning
confidence: 99%
“…1A) modulated viral replication ability. Furthermore, we found that these variations in SA1prox affected HIV-1 mRNA expression patterns, especially its vif mRNA levels, thereby suggesting a role of this region in viral gene expression (6).…”
mentioning
confidence: 81%
See 3 more Smart Citations